IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DARING PADA MASA COVID-19 DI SMPN 9 BANJARBARU - Nizami, Ahmad Wafa; Ramadhan, Mufti; Nazif, Ahmad; Aziz, Muhamaad Azmi (ADDABANA: Jurnal Pendidikan Agama Islam, 2020)
Abstract: This research discusses the "Implementation of Online Islamic Religious Education Learning during the Covid-19 Period at SMPN 9 Banjarbaru". The formulation of the problem in this study is how the Implementation of Online Islamic Religious Education Learning during the Covid-19 Period at SMPN 9 Banjarbaru and its supporting and inhibiting aspects. The purpose of this research is to find out the Implementation of Online Islamic Religious Education Learning during the Covid-19 Period at SMPN 9 Banjarbaru as well as its supporting and inhibiting aspects.The subject of this research is the Islamic Religious Education teacher of SMPN 9 Banjarbaru while the object of this research is the Implementation of Online Islamic Religious Education Learning during the Covid-19 period at SMPN 9 Banjarbaru as well as its supporting and inhibiting aspects. In extracting data, researchers used observation, interview and documentation techniques. Data management techniques are carried out by data classification, editing, and data interpretation. Furthermore, it was analyzed with qualitative descriptive analysis and inductive conclusions were drawn.Based on the results of the study, it is known that the Implementation of Online Islamic Religious Education Learning during the Covid-19 period at SMPN 9 Banjarbaru in its implementation has been running well in accordance with the procedures of the Ministry of Education, Culture, Research and Technology (KEMENDIKBUD).  The implementation of online learning in general can be seen from the Islamic Religious Education teacher in carrying out learning using an online system with whatsapp application online media facilities by applying to students, students are familiarized and directed to do good habits such as maintaining environmental cleanliness and always being monitored to collect assignments on time. Aspects that support online learning include educational background, teaching experience, and the personality of Islamic Religious Education teachers. Keywords: Covid-19, Online, Islamic Religious Education Learning. Abstrak: Penelitian ini membahas tentang “Implementasi Pembelajaran Pendidikan Agama Islam Daring Pada Masa Covid-19 di SMPN 9 Banjarbaru”. Rumusan masalah dalam penelitian ini adalah bagaimana Implementasi Pembelajaran Pendidikan Agama Islam Daring Pada Masa Covid-19 di SMPN 9 Banjarbaru serta aspek pendukung dan penghambatnya. Tujuan penelitian ini ialah untuk mengetahui Implementasi Pembelajaran Pendidikan Agama Islam Daring Pada Masa Covid-19 di SMPN 9 Banjarbaru serta aspek pendukung dan penghambatnya.Subjek dalam penelitian ini ialah guru Pendidikan Agama Islam SMPN 9 Banjarbaru sedangkan objek dalam penelitian ini adalah Implementasi Pembelajaran Pendidikan Agama Islam Daring Pada Masa Covid-19 di SMPN 9 Banjarbaru serta aspek pendukung dan penghambatnya.Dalam penggalian data, peneliti menggunakan teknik observasi, wawancara dan dokumentasi. Teknik pengelolaan data dilakukan dengan klasifikasi data, editing, dan interpretasi data. Selanjutnya dianalisis dengan analisa deskriptif kualitatif dan ditarik simpulan secara induktif.Berdasarkan hasil penelitian, diketahui bahwa Implementasi Pembelajaran Pendidikan Agama Islam Daring Pada Masa Covid-19 di SMPN 9 Banjarbaru dalam pelaksanaanya sudah berjalan dengan baik sesuai dengan prosedur Kementrian Pendidikan, Kebudayaan, Riset, dan Teknologi (KEMENDIKBUD).  Pelaksanaan pembelajaran daring pada umumnya terlihat dari guru Pendidikan Agama Islam dalam melaksanakan pembelajaran menggunakan system daring dengan fasilitas media online aplikasi whatsapp dengan melakukan penerapan kepada siswanya, siswa di biasakan dan diarahkan untuk melakukan kebiasaan baik seperti menjaga kebersihan lingkungan serta selalu di pantau untuk mengumpulkan tugas tepat waktu. Aspek yang mendukung pembelajaran daring tersebut antara lain berasal dari latar belakang pendidikan, pengalaman mengajar, dan kepribadian guru Pendidikan Agama Islam. Kata Kunci: Covid-19, Daring, Pembelajaran Pendidikan Agama Islam.